SUMBER PENCEMAR YANG MEMPENGARUHI KUALITAS AIR SUNGAI MUMBUL DI KELURAHAN BANJARJAWA, KAMPUNG ANYAR KABUPATEN BULELENG - IN SUWIRTA; I.W. Budiarsa Suyasa; M.S. Mahendra (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Sungai Mumbul is one of the potential water resources to be an alternative to meet the need for clean water in particular urban communities in Singaraja (Buleleng) including Banjar Jawa and Kampung Anyar, but its existence need protection from activities in their environment. The objectives of this re.search are: (1) to determine the physical, chemistry, and microbiology of water quality, (2) to determine 1he pollutant load in the sea/ocean, and (3) to determine the activity of people which decrease wate: quality of Sungai Mumbul. The sampling method was purposipe sampling in which the samples were, taken at 5 point.:; Q 0 (source of water), Q1 -out (Kaltag water) with a sampling frequency of once a day every two weeks for one month, On Qout, samples were taken 3 times: in the morning, afternoon and evening. Sampel were analys in laboratory. The results were compared with Bali Governor Regulation No. 8 of 2007 and water quality status of water quality refers to the the Environment Decree No 115 of 2003. Load of pollutants COD rrnc1. BOD s (laboratory measurements). Activities of communities obtained from observations by identifying the number of facilities. The results showed that, in general, water quality parameters of Sungai Mumbul such as temperature, TDS, pH, Sulfate, ammonia, and nitrates were still below the threshold quality standards, while the parameters of COD, BOD5, nitrites, sulfides, oils grease, faecal coliform and total coliform exceeded the quality standard, with quality status categories were polluted, and the total value/score was -30. The use of the residential waste disposal fasilities allowing a lower water quality of Sungai Mumbul the primary channel of 172 units (13:26%), the secondary channel of 426 units (32.85%), tertiary of 396 units (30.53%), and the internal channel of 303 units (23.36%) . Load pollutants that lead to the beach/ sea of Kampung Anyar for BOD 5 indicator was 434,12 kg/day, and COD load of 1,033 kg/day.